Disrespect and abuse during childbirth in East Hararghe Zone public health facilities, eastern Ethiopia: a cross-sectional study - Usso, Ahmedin Aliyi; Adem, Hassen Abdi; Alemu, Addisu; Mohammed, Aminu (Frontiers in Global Women's Health, 2023)
Background Compassionate and respectful maternity care during childbirth has been identified as a potential strategy to prevent and reduce maternal mortality and morbidity. Despite its importance, there is a paucity of information on the level of disrespect and abuse meted out to mothers in eastern Ethiopia. This study assesses the level of disrespect and abuse suffered by women during childbirth, and the associated factors, in public health facilities in the rural East Hararghe Zone in eastern Ethiopia. Methods A cross-sectional study was conducted among 530 women who gave birth in 20 public health facilities in the East Hararghe Zone during the period between 1 April and 30 April 2020. Data were collected using a validated questionnaire. Bivariable and multivariable binary logistic regression analyses were employed to identify the factors associated with disrespect and abuse during childbirth. Adjusted odds ratio (AOR) (95% CI) was used to report this association, and statistical significance was set at P < 0.05. Results Overall, 77% (95% CI: 73%–81%) of women reported at least one type of disrespect and abuse during childbirth in the East Hararghe Zone public health facilities. In this study, factors such as households having an average monthly income of below 57.22 USD (AOR = 2.29, 95% CI: 1.41–3.71), mothers residing at more than 30 min away from a nearby health facility (AOR = 2.10, 95% CI: 1.30–3.39), those not receiving antenatal care (AOR = 4.29, 95% CI: 2.17–8.52), and those giving birth during nighttime (AOR = 2.16, 95% CI: 1.37–3.41) were associated with at least one type of disrespect and abuse during childbirth. Conclusion More than three in every four women who gave birth in the East Hararghe Zone public health facilities were disrespected and abused during childbirth. Encouraging all pregnant women to pay attention to antenatal care visits and improving the quality of healthcare service during nighttime in all health facilities will be essential for preventing and reducing disrespect and abuse and its negative consequences.